Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae) - Zaragoza, Juan A. (Zootaxa, 2017)
A taxonomic revision of the subgenus Chthonius (Ephippiochthonius) in the Iberian Peninsula, Balearic Islands and    Macaronesia is presented. New and previously insufficiently studied characteristics are shown to be taxonomically useful, such as the chelal lyrifissures patterns, chaetotaxy and condylar complex. Three taxa previously treated as subgenera of Chthonius are here raised to generic rank: Ephippiochthonius n. stat., Globochthonius n. stat., and Hesperochthonius n. stat. Two new genera are described: Cantabrochthonius n. gen. and Occidenchthonius n. gen. Thirty-five new species are described: Ephippiochthonius aini n. sp., E. andalucia n. sp., E. aurouxi n. sp., E. benimaquia n. sp., E. caceresi n. sp., E. castellonensis n. sp., E. comasi n. sp., E. fadriquei n. sp., E. galcerani n. sp., E. gonzalezi n. sp., E. henderickxi n. sp., E. ibiza n. sp., E. masoae n. sp., E. portugalensis n. sp., E. riberai n. sp., E. serengei n. sp., E. sevai n. sp., E. tarraconensis n. sp., E. vicenae n. sp., E. zaballosi n. sp., Occidenchthonius anae n. sp., O. beieri n. sp., O. ebo n. sp., O. felgueraorum n. sp., O. gardinii n. sp., O. hoerwegi n. sp., O. lencinai n. sp., O. mahnerti n. sp., O. mateui n. sp., O. montagudi n. sp., O. murcia n. sp., O. oromii n. sp., O. ortunoi n. sp., O. riopar n. sp. and O. serranoi n. sp. A neotype is designated for Ephippiochthonius catalonicus (Beier, 1939), n. comb. As result of the changes in generic rank, 45 new combinations for species are proposed.